2010
DOI: 10.1212/wnl.0b013e3181d3e2dd
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter perfusion correlates with disease severity in ALS

Abstract: Amyotrophic lateral sclerosis (ALS) severity is correlated with brain perfusion as measured by arterial spin labeling (ASL) perfusion. This correlation appears to be independent of brain atrophy. ASL perfusion may be a useful tool for monitoring disease progression and assessing treatment effects in ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 20 publications
7
53
2
1
Order By: Relevance
“…Moreover, this is not the first study in which ALS effects were manifest as lateralized in the motor system. 4,10,15,20,37,43,44 Our findings are also in agreement with the descriptions of asymmetry in ALS pathology of the CSTs, 45 though a correspondence between the side of greater MR imaging differences and the side of greater muscle strength deficit of the limbs was not found, 10 probably because the muscle-strength score is a result of the upper and lower motor neuron involvement, whereas MR imaging detects only the UMN damage.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, this is not the first study in which ALS effects were manifest as lateralized in the motor system. 4,10,15,20,37,43,44 Our findings are also in agreement with the descriptions of asymmetry in ALS pathology of the CSTs, 45 though a correspondence between the side of greater MR imaging differences and the side of greater muscle strength deficit of the limbs was not found, 10 probably because the muscle-strength score is a result of the upper and lower motor neuron involvement, whereas MR imaging detects only the UMN damage.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study of arterial spin-labeling MR imaging in patients with ALS found that the severity of upper motor neuron involvement as measured by finger tapping correlated with perfusion of the middle cingulate gyrus. 31 We are aware of a single MRSI study of the anterior cingulate in ALS; it showed reduced NAA/Cr specifically in those with bulbar onset disease. 32 Convincing evidence for thalamic involvement in ALS has not been forthcoming from routine postmortem or standard anatomic imaging studies.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, patients with progressive muscular atrophy appeared to have normal or near-normal cerebral metabolism and CBF [74,75]. A recent study in ALS showed similar findings using ASL perfusion [21]. These authors also found regional areas where increased ALS severity correlated with decreased gray matter perfusion, suggesting that measurement of brain perfusion may be another useful tool for monitoring disease progression and assessing treatment effects in ALS (FIG.…”
Section: Clinical Applicationmentioning
confidence: 73%
“…The dashed lines indicate the extent of the brain that was covered by the ASL perfusion images. Reproduced with permission from Rule et al [21]. (High resolution version of this image is available in the electronic supplementary material.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation